Evaluasi Peran Perjanjian Perdagangan Internasional, Penyesuaian Kebijakan Moneter, Dan Inovasi Teknologi Dalam Mendorong Stabilitas Makroekonomi Dan Pertumbuhan Inklusif Di Negara Berkembang - Ilmi, Raihanah Ghoniyyah (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study examines the role of international trade agreements, monetary policy adjustments, and technological innovation in promoting macroeconomic stability and inclusive growth in developing countries. Using panel data analysis covering 35 developing countries from 2005 to 2023, the study finds that trade openness significantly enhances per capita GDP growth and strengthens economic resilience to global shocks. Adaptive monetary policies, including interest rate adjustments and inflation control, contribute to macroeconomic stability. Technological innovation, measured through digital adoption, R&D investment, and patent registrations, positively impacts productivity and income distribution, fostering inclusive growth. The analysis further reveals that the synergistic interaction among trade, monetary policy, and technology amplifies their individual effects. The study highlights the importance of coordinated and evidence-based policy frameworks to achieve sustainable and inclusive economic development in developing countries.